3D Pharmacophore-based Ligand Alignment, Virtual Screening and Molecular Docking Protocols Towards the Discovery of 2-((1H-1,2,4-triazol-1- yl)methyl) Derivatives as Antifungal Inhibitors - Badawy, Mohamed E. I.; El-Zemity, Saad R. (Current Bioactive Compounds, 2020)
Background: 1,2,4-Triazoles are important five-membered heterocyclic scaffolds due to their extensive biological activities. These products have been an area of growing interest to many researchers around the world as of their diverse biological activities including antifungal and antibacterial activity against broad spectrum of microbial pathogens. Methods: A series of 2-((1H-1,2,4-triazol-1-yl)methyl) derivatives was designed, synthesized and evaluated as antifungal agents against five plant pathogenic fungi (Alternaria tennis, Botryodiplodia theobromae, Fusarium moniliforme, Fusarium oxysporum and Helminthosporium turcicum) to meet the urgent need of new antifungal agents with improved activity and broader spectrum. In silico studies including pharmacophore modeling, virtual screening, drug-likeness analysis and ADMET prediction were examined. In addition, the elucidation of the activity is based on the molecular docking to the active site of the Sterol 14α-Demethylase Cytochrome P450 (CYP51) was investigated. Results: The results of antifungal activity indicated that the compounds containing tert or sec-butyl as hydrophobic substituents on a phenyl ring significantly increased the activity (compounds 4, 5 and 6) with EC50 in the range of 8-84 mg/L of all tested fungi. The pharmacophore modeling produced an accurate projecting model (Hypo 1) from these derivatives. The superlative Hypo1 consists of three features counting two hydrogen bond acceptors (HBA) and one hydrophobic (HYD). The docking results showed approximately a similar binding degree at the active sites of the fungal enzyme (CYP51) as a standard fungicide penconazole. Conclusion: According to data obtained, some derivatives, especially those with tert or sec-butyl substituents on the phenyl ring, were more potent against phytopathogenic fungi. These compounds (e.g., 4, 5, and 6) should develop into new potential fungicides as a desirable activity.
Keywords: virtual screening